2019
DOI: 10.1111/1541-4337.12503
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Plasma–Liquid Interactions in Food Processing: A Review

Abstract: Nonthermal processing methods are often preferred over conventional food processing methods to ensure nutritional quality. Nonthermal plasma (NTP) is a new field of nonthermal processing technology and seeing increased interest for application in food preservation. In food applications of NTP, liquid interactions are the most prevalent. The NTP reactivity and product storability are altered during this interaction. The water activated by NTP (plasma‐activated water [PAW]) has gained considerable attention duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 179 publications
(415 reference statements)
1
55
0
1
Order By: Relevance
“…H 2 O 2 is considered to be a potent anti-microbial agent. Several studies have investigated about the importance of H 2 O 2 to the antimicrobial activity of PAW 18,25 . In this study, concentration of H 2 O 2 was generated in PAW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 O 2 is considered to be a potent anti-microbial agent. Several studies have investigated about the importance of H 2 O 2 to the antimicrobial activity of PAW 18,25 . In this study, concentration of H 2 O 2 was generated in PAW.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma has been mainly used in bio-medical, textile and polymer industries 14 16 . However, recent studies have demonstrated potential applications of plasma technology in the food industry 17 , 18 . There is a range of different approaches to generate plasma discharges, using different geometry configuration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reactions between newly formed species results in a decrease in the pH; the synergistic effect of high oxidation-reduction potential and low pH has proved to be the basis of the bactericidal properties of PAW. 56,57 Figure 3 shows the decontamination mechanism of PAW. 57 In an exemplified study, Ma et al 58 observed that the total number of S. aureus in PAW-treated strawberry decreased by 1.6-2.3 log.…”
Section: Combined Ultrasonic Cleaning With Ozonementioning
confidence: 99%
“…56,57 Figure 3 shows the decontamination mechanism of PAW. 57 In an exemplified study, Ma et al 58 observed that the total number of S. aureus in PAW-treated strawberry decreased by 1.6-2.3 log. After 4 days of storage, S. aureus on the strawberry was still 1.7-3.4 log lower than that on the untreated strawberry.…”
Section: Combined Ultrasonic Cleaning With Ozonementioning
confidence: 99%
“…4 In agriculture and food processing, CAP has been applied to different biosubstances directly or through plasma-activated media such as water or water mist to increase productivity or fight diseases and pathogens. 5,6 Wheat is one of the most strategic crops for increasing food security, 7 and CAP has been revealed as a valuable method for enhancing wheat seed germination. 8,9 During wheat seed plasma treatment, CAP by its uniform behavior can replace traditional presowing treatment, either physically or chemically.…”
Section: Introductionmentioning
confidence: 99%